Spatial and temporal dynamic of the trophic state in a large Amazonian hydroelectric reservoir - Curtarelli, M. P.; Ogashawara, I.; Alcantara, E. H. [UNESP]; Lorenzzetti, J. A.; Stech, J. L. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
We assessed the spatial and temporal dynamic of the trophic state in a large Amazonian hydroelectric reservoir during the Austral wintertime using images acquired by the Operational Land Imager (OLI) sensor on board the Landsat 8 satellite. We used the Spectral Angle Mapper (SAM) algorithm and reference in situ spectra to classify the OLI images according to a trophic state index (TSI). The results showed that the use of OLI images and the SAM algorithm were suitable for the mapping of the TSI in the Amazonian reservoirs. In our particular case, the reservoir presented a high spatial and temporal heterogeneity in the TSI during the studied period. However, further studies are needed to better characterize the dynamics of the trophic state and its driven forces.
Keywords: Amazon; hydroelectric reservoir; remote sensing; spectral angle mapper; trophic state index